Quickest detection of an abrupt change in a random sequence with finite change-time - Yong Liu; Blostein, S.D. (IEEE transactions on information theory, 1994)
This paper proposes a new procedure for quickest detection of an abrupt change in a random sequence, where a change is known to occur with probability one. Applications include on-line speech segmentation, edge detection in image processing, and communications channel monitoring. In contrast to Shiryayev's (1963) problem formulation, prior knowledge of a change-time distribution is not required. The optimality criterion considered is similar to Shiryayev's, except that the expected delay is to be minimized subject to both overall false alarm probability and false alarm average run length constraints under this criterion, theoretical study shows that the new procedure approximates an optimal but unrealizable Bayesian procedure, particularly for small signal changes or for low probability of false alarm. Simulations confirm that under such conditions, the new procedure compares favorably with Page's (1954) CUSUM, an optimized moving-window fixed-sample-size (FSS) procedure, and a special ease of the Girshick-Rubin-Shiryayev (1952) procedure.< >